A prosthetic and surgical approach for full-arch rehabilitation in atrophic maxilla previously affected by peri-implantitis - Pavanelli, Angélica Letícia Reis [UNESP]; De Avila, Erica Dorigatti [UNESP]; Barros-Filho, Luiz Antônio Borelli [UNESP]; De Assis Mollo, Francisco [UNESP]; Cirelli, Joni Augusto [UNESP]; Borelli Barros, Luiz Antônio [UNESP]; De Molon, Rafael Scaf [UNESP] (Wiley, 2021)
Rehabilitation of atrophic maxilla with dental implants is still a challenge in clinical practice especially in cases of alveolar bone resorption due to peri-implantitis and pneumatization of the maxillary sinuses. Several surgical approaches have been employed to reconstruct the lost tissues allowing the proper tridimensional position of the implants. In this context, the aim of this case report is to describe a surgical and prosthetic approach to fully rehabilitate the atrophic maxilla with dental implants. The patient presented with unsatisfactory functional and esthetical implant-supported prosthesis with some of the implants already lost by peri-implantitis. The remaining three implants were also affected by peri-implantitis. Reversal prosthetic planning was performed, and a provisional prosthesis was fabricated and anchored in two short implants. Sinus floor augmentation procedure and onlay bone graft were then accomplished. After a healing period of 8 months, digital-guided surgery approach was performed to place the implants. Finally, a definitive prosthesis was installed. One-year follow-up has revealed stabilization of the bone tissue level, successful osseointegration, and a pleasant esthetic and functional result. A proper diagnosis and careful planning play an important role to enhance precision and to achieve patient esthetic and functional outcomes.